Prevention and Rehabilitation of the Athletic Hamstring Injury - Adriana Geraci, P.T., D.P.T.; Delaney Mahon, P.T., D.P.T.; Eric Hu, B.S.; Jesus E. Cervantes, B.S.; Shane J. Nho, M.D., M.S. (Arthroscopy, Sports Medicine, and Rehabilitation)
Hamstring injuries are a common occurrence in both recreational and competitive athletes. Professional athletes have an increased incidence of hamstring-related injuries because most of these injuries are often attributed to movements involving forceful and rapid hamstring lengthening. The incidence of hamstring injuries is particularly high in professional baseball players, likely due to the high-speed running and frequent transition from static standing to dynamic movements inherent to the sport itself. To improve an athlete’s ability to return to sport and minimize days off due to injury, a programmed rehabilitation program combining a range of training parameters that ensure the athlete can work near the limit of their capacity while concurrently allowing sufficient time for the injured tissue to heal is essential. The purpose of this article is to summarize the different features and evaluation of hamstring injuries in athletes, highlight evidence-based rehabilitation interventions, and identify preventative strategies to effectively and efficiently treat athletes, particularly baseball players, with hamstring injuries. Level of Evidence: Level V, expert opinion.